Worship. Vor 300 Jahren erklang Bachs Magnificat - Schroeter-Wittke, Harald (Praktische Theologie)

Cryogenic reverse flow forming of AISI 304L - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank (Materials Research Proceedings)
Abstract. Workpiece property-control permits the application-oriented and time-efficient production of components. In reverse flow forming, for example, a control of the microstructure profile is not yet part of the state of the art, in contrast to the geometry control. This is, due to several reasons, particularly challenging when forming seamless tubes made of metastable austenitic stainless AISI 304L steel. Inducing mechanical and/or thermal energy can cause a phase transformation from austenite to martensite within this steel. The resulting α’-martensite has different mechanical and micromagnetic properties, which can be advantageous depending on the application. For purposes of local property control, the resulting α’-martensite content should be measured and controlled online during the forming process. This paper presents results from the usage of a custom developed cryo-system and different application strategies to use liquid nitrogen as a coolant for local enhancement of the forming-temperature depending α’-martensite content.

La Belgique à travers les textes – Potenziale des sprachlichen und soziokulturel¬len Wissenserwerbs - Bürgel, Christoph; De Knop, Sabine (Belgien – anregend anders: Fachwissenschaft und Fachdidaktik untersuchen die Vielfalt der Sprachen, Literaturen und Kulturen in Belgien)

Rendez-vous à quelle heure ? Kommunikativer Transfer von Uhrzeiten in einen Verabredungsdialog - Bürgel, Christoph (Der Fremdsprachliche Unterricht Französisch)

Et maintenant, faites un dialogue ! Dialogisches Sprechen optimal fördern - Bürgel, Christoph (Der Fremdsprachliche Unterricht Französisch)

Dynamics-induced charge transfer in semiconducting conjugated polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Dynamics-induced interchain charge transfer in a polymer aggregate in stack configuration can be understood by single-oligomer polaron energy.
Keywords: Materials Chemistry; General Chemistry

Monitoring the evolution of dimensional accuracy and product properties in property-controlled forming processes - Stebner, Sophie Charlotte; Arian, Bahman; Martschin, Juri; Dietrich, Stefan; Feistle, Martin; Hütter, Sebastian; Lafarge, Rémi; Laue, Robert; Li, Xinyang; Schulte, Christopher; Spies, Daniel; Thein, Ferdinand; et al. (Electrical Engineering: Systems and Control)

Zusammenarbeit von Frühförderung und Kita im Förderschwerpunkt Sehen - Jesuthasan, Jonitta

Australien und Neuseeland als Projektionen des Südens in deutschsprachiger Gegenwartslyrik von Jan Wagner und Ulrike Almut Sandig - Elit, Stefan (Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann)

Reflections on Music in Fiction: Rose Tremain’s Music and Silence (1999), Julian Barnes’s The Noise of Time (2016) and Roger Scruton’s Perictione in Colophon (2000) - Mildorf, Jarmila (Anglia)

Untersuchung der UVC-Bestrahlung als Oberflächenvorbehandlungsmethode von Polycarbonaten zur Erzeugung einer Verbundhaftung zu Flüssigsilikonkautschuken - Hartung, Michael

An approach for the numerical calculation of the non-isothermal pressure-throughput-characteristics of single screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of the influence of process and screw configurations on fiber length for recycled carbon fiber - Malatyali, Hatice; Schöppner, Volker; Hoemann, Theresa (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of shear rates in twin-screw extruder using CFD-simulation - Malatyali, Hatice; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

"English was British". Reflecting on language in a globalized world through an excerpt from Naoise Dolan’s novel Exciting Times - Janzen, Thomas; Methfessel, Annette (Englisch betrifft uns)

Influence of fiber geometry and sizing on glass fiber breakage - Bürenhaus, Franziska Isabelle; Moritzer, Elmar (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Meta-Reinforcement-Learning-Based Current Control of Permanent Magnet Synchronous Motor Drives for a Wide Range of Power Classes - Jakobeit, Darius; Schenke, Maximilian; Wallscheid, Oliver (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

"Belgische Literatur in deutscher Übersetzung. Ein Interview mit der Übersetzungswissenschaftlerin Anja Van de Pol-Tegge" (PODCAST) - Huybrechts, Yves

"Vlaanderen Feest! - Der flämische Feiertag 2023" (VIDEO) - Huybrechts, Yves

Österreich zwischen Vorbildfunktion und Eigeninteresse. Der Fall Jever, 1737-1739 - Huybrechts, Yves (Konkurrenzen in der Frühen Neuzeit: Aufeinandertreffen - Übereinstimmung - Rivalität)